Preparing Your Own Fish Feeds - Juli-Anne B. Royes; Frank A. Chapman (EDIS, 2003)
This paper presents examples of: 1) Experimental and practical fish feed blends or formulas which are nutrient balanced and adaptable to particular conditions; 2) The formulation and preparation of a semi-purified ornamental African cichlid fish diet that can be used in the laboratory or when small quantities of feed are needed; 3) The preparation of a gelatin-based diet that is often used to administer medicines or other chemicals.  Background information on nutrition, feedstuffs and feed formulations are presented with emphasis primarily on the feeding of ornamental “aquarium” fishes. First published Feburary 2003.